2006
DOI: 10.1002/path.2061
|View full text |Cite
|
Sign up to set email alerts
|

Renal prothrombin mRNA is significantly decreased in a hyperoxaluric rat model of nephrolithiasis

Abstract: Although urinary prothrombin fragment 1 (UPTF1) possesses several hallmarks expected of a regulatory protein in urolithiasis, its precise role remains unknown. To determine the relationship between renal prothrombin (PT), the parent molecule of UPTF1, and lithogenesis, this study quantified and compared levels of renal PT mRNA in healthy rats (n = 10) and rats rendered lithogenic (n = 10) by ingestion of 0.75% ethylene glycol for 8 weeks. Studies included morphological and histological examination of the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…92 The exposure of renal epithelial cells to oxalate causes oxidative damage, mitochondrial damage, activation of second messenger path ways (such as those mediated by p38 MAP kinase and phospholipase A), inflammatory response signaling, changes in the expression of putative modulators of crystallization (such as osteopontin, bikunin and Tamm-Horsfall protein), and changes in the glycocalyx. [93][94][95][96][97][98][99][100][101][102][103][104] The effects of oxalate on renal epithelial cells have been extensively discussed by Jonassen et al 105 Although some of these effects are directly due to oxalate, others are secondary to oxalate induced oxidative damage or inflammatory responses. 96,106 The changes effected by oxalate could promote nephrolithiasis by providing debris for crystal nucleation, making the apical plasma membrane more adhesive to crystals, or altering the availability of crystallizationinhibiting proteins.…”
Section: Potential Roles Of Oxalate In Nephrolithiasismentioning
confidence: 99%
“…92 The exposure of renal epithelial cells to oxalate causes oxidative damage, mitochondrial damage, activation of second messenger path ways (such as those mediated by p38 MAP kinase and phospholipase A), inflammatory response signaling, changes in the expression of putative modulators of crystallization (such as osteopontin, bikunin and Tamm-Horsfall protein), and changes in the glycocalyx. [93][94][95][96][97][98][99][100][101][102][103][104] The effects of oxalate on renal epithelial cells have been extensively discussed by Jonassen et al 105 Although some of these effects are directly due to oxalate, others are secondary to oxalate induced oxidative damage or inflammatory responses. 96,106 The changes effected by oxalate could promote nephrolithiasis by providing debris for crystal nucleation, making the apical plasma membrane more adhesive to crystals, or altering the availability of crystallizationinhibiting proteins.…”
Section: Potential Roles Of Oxalate In Nephrolithiasismentioning
confidence: 99%
“…In addition, production of crystallization modulators, such as osteopontin (Opn) (41,76,78), Tamm-Horsfall protein (Umod, uromodulin) (13,58), urinary prothrombin fragment-1 (Uptf-1) (17,18), bikunin (Bk) (32), and inter-␣-trypsin inhibitors (Itih) (61), is altered when cells are exposed to CaOx crystals. In support of this, we have shown that inhibition of NADPH oxidase reduces the production of Opn by renal epithelial cells exposed to CaOx crystals, while CaOx monohydrate crystal exposure of renal epithelial NRK52E cells, pretreated with the NADPH oxidase inhibitor diphenyleneiodium (DPI), reduced the production of ROS compared with cells not treated with DPI (78).…”
mentioning
confidence: 99%
“…We propose that the minor (C) allele of SNP rs5896 (encoding threonine) – a protective allele for KSD, which is significantly more frequent in the control group than in the patient group, conserves the glycan site of UPTF1 and influences the UPTF1 inhibitory activity function in protection against CaOx crystallization. F2 mRNA was found to significantly reduce in kidney of a hyperoxaluric rat model of nephrolithiasis [23] and many features of UPTF1 function have been studied [21], [22], [24], [25]. However, the precise mechanism of KSD with respect to UPTF1 remains unclear.…”
Section: Discussionmentioning
confidence: 99%